Rational form of semi-finished vegetables and device for slicing them - Parenuk, Irina; Lulka, Alexander; Polovyk, Volodymyr (My University, 2017)
The rational form of semi-finished vegetables for stuffing has been developed, the range of cutting vegetables has been expanded. The device for slicing vegetable semi-rational form has been developed.
Keywords: харчова цінність; nutritional value; солодкі страви; sweet dishes; кафедра готельно-ресторанної справи; кафедра технології ресторанної і аюрведичної продукції